Malignant pleural mesothelioma with heterologous elements. Issue 10 (10th August 2021) - Kawai, Toshiaki; Seki, Reishi; Miyajima, Kuniharu; Nakashima, Hiroshi; Takeda, Takayuki; Murakami, Tomoyuki; Aoe, Keisuke; Okabe, Kazunori; Homma, Keiichi; Tsukamoto, Yoshitane; Sunada, Koichi; Terasaki, Yasuhiro; et al.
Abstract : Aims: Malignant pleural mesothelioma with heterologous elements (such as osseous, cartilaginous or rhabdomyoblastic differentiation) is very rare. We tried to differentiate such mesothelioma cases from extraskeletal pleural osteosarcoma, which is very challenging. Methods: We compared 10 malignant pleural mesotheliomas (three biphasic and seven sarcomatoid types) with two pleural osteosarcomas using clinicopathological and immunohistochemical methods, and also fluorescence in situ hybridisation (FISH) to examine for homozygous deletion of p16. Results: The median age was 72 years for mesotheliomas, and 69 years for osteosarcoma. For mesothelioma, eight cases were male and two were female. Growth was diffuse in all mesothelioma cases except case 10, where it was localised, as it was for the two osteosarcomas. Among mesothelioma cases, 80% displayed osteosarcomatous and 60% chondromatous elements, while 10% exhibited rhabdomyoblastic ones. Immunohistochemical labelling for calretinin and AE1/AE3 was present in 8/10 and 7/10 mesotheliomas, respectively, but in only one osteosarcoma. Loss of methylthioadenosine phosphorylase was seen in 5/7 mesotheliomas. FISH analysis revealed homozygous deletion of p16 in 5/8 mesothelioma and 2/2 osteosarcoma. Median survival was 6.5 months after biopsy or surgical operation in mesothelioma, and 12 months after operation in osteosarcoma. Conclusions: Although median survival was longer for osteosarcoma than for malignant mesothelioma, we could not differentiate mesothelioma from pleural osteosarcoma on the combined basis of clinicopathological and immunohistochemical data, and FISH analysis. However, diffuse growth was more frequent in mesothelioma than in osteosarcoma.